2012
DOI: 10.1007/s00114-012-0921-5
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ultra-weak light emissions from wheat seedlings are rhythmic and synchronized with the time profile of the local gravimetric tide

Abstract: Semi-circadian rhythms of spontaneous photon emission from wheat seedlings germinated and grown in a constant environment (darkened chamber) were found to be synchronized with the rhythm of the local gravimetric (lunisolar) tidal acceleration. Time courses of the photon-count curves were also found to match the growth velocity profile of the seedlings. Pair-wise analyses of the data--growth, photon count, and tidal--by local tracking correlation always revealed significant coefficients (P > 0.7) for more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…This is within the range of the radiant flux density of photon fields emitted from living cerebral tissue [14]. Recently Moraes et al [15] showed that spontaneous ultra-weak light emissions from wheat seedlings were synchronized with the gravimetric tide, more specifically the lunisolar tidal accelerations.…”
Section: Borowski Graviational Pressure Equivalentsmentioning
confidence: 69%
“…This is within the range of the radiant flux density of photon fields emitted from living cerebral tissue [14]. Recently Moraes et al [15] showed that spontaneous ultra-weak light emissions from wheat seedlings were synchronized with the gravimetric tide, more specifically the lunisolar tidal accelerations.…”
Section: Borowski Graviational Pressure Equivalentsmentioning
confidence: 69%
“…Analyses of new as well as of old UPE series data in germination tests showed similar results to those presented by Zürcher et al (44) and Barlow et al (45). Autocorrelation and local correlation (Pearson) functions and fast Fourier transformation were used to show that UPE singular pointscurve jumps and plateaus (see http://www.ft.unicamp.br/gallep/Gerais/ complete1and2.pdf)are synchronous with local peaks/droughts of the local gravimetric (tide) pattern (δg), and that UPE and δg present equivalent periodicities (46). A sort of acclimatization of those cycles was also found for seeds transported overseas when compared to local and non-transported samples (47).…”
Section: Recent Results: Lafa Datamentioning
confidence: 99%
“…This is the typical duration of the hydronium ion before the extra proton is displaced to the next water molecule [10]. Considering the presence of water on the solar surface [20], primarily within the localized solar vortices where lower temperature prevail (sunspots) the potential for excess correlation between terrestrial and solar sources could allow a different perspective for the many "correlations" between solar activity and both chemical and biological reactions that depend upon the dynamics of water [21][22][23][24][25]. Such a relationship could reclassify these phenomena from eccentric chemical anomalies or observation artifacts to predictable properties of some aqueous solutions when Schrodinger-type entanglement occurs.…”
Section: Discussionmentioning
confidence: 99%